Rhizobium meliloti nodulation genes allow Agrobacterium tumefaciens and Escherichia coli to form pseudonodules on alfalfa. - Hirsch, A M (1984)
Regions of the Rhizobium meliloti symbiotic plasmid (20 to 40 kilobase pairs long) containing nodulation (nod) genes were transferred to Agrobacterium tumefaciens or Escherichia coli by conjugation. The A. tumefaciens and E. coli transconjugants elicited root hair curling and the formation of ineffective pseudonodules on inoculated alfalfa plants. A tumefaciens elicited pseudonodules formed at a variable frequency, ranging from 15 to 45%, irrespective of the presence of the Ti plasmid. These pseudonodules developed characteristic nodule meristems, and in some nodules, infection threads were found within the interior of nodules. Infrequently, infection threads penetrated deformed root hairs, but these threads were found only in a minority of nodules. There was no evidence of bacterial release from the infection threads. In addition to being found within threads, agrobacteria were also found in intercellular spaces and within nodule cells that had senesced . In the latter case, the bacteria appeared to invade the nodule cells independently of infection threads and degenerated at the same time as the senescing host cells. No peribacteroid membranes enclosed any agrobacteria , and no bacteroid differentiation was observed. In contrast to the A. tumefaciens-induced pseudonodules , the E. coli-induced pseudonodules were completely devoid of bacteria; infection threads were not found to penetrate root hairs or within nodules. Our results suggest that relatively few Rhizobium genes are involved in the earliest stages of nodulation, and that curling of root hairs and penetration of bacteria via root hair infection threads are not prerequisites for nodule meristem formation in alfalfa.